Emotional Contagion Sebagai Produk Dari Budaya Organisasi Studi Kasus Pada Parahyangan Residence - Vincent; Rusli Ginting Munthe (Eastasouth Institute, 2023)
Service organizations encourage employees to express positive emotions in service transactions with customers, with the hope that customers can capture these emotions and have positive reactions where customers become satisfied in enjoying service sector services. The service process is known as emotional contagion. However, this is a challenge for employees to be able to continue to display positive emotions during service where in the end they will fake their emotions and act (surface acting and deep acting) during the service process. The researcher uses a case study at a service sector company in Bandung and finds that the implementation of emotional contagion is dominated by organizational motives that are driven by organizational culture. This prompted the receptionist to display false positive emotions with deep acting.